(untitled) (Research, Society and Development, 2021)
Odontogenic infections are complications commonly faced by dentists after third molar extraction, thus, it is extremely important that maxillofacial surgeons know how to correctly diagnose and treat these cases. Thus, the objective is to report a clinical case of a 20-year-old female patient with severe odontogenic infection. Leukoderma patient, with extensive volumetric increase on the right side, history of previous extraction of a dental element with a picture of pericoronitis prior to extraction, admitted by the Maxillofacial Surgery and Traumatology Service of Hospital Universitário Maria Aparecida Pedrossian. Extensive edema in the right submandibular region, dyspnea, dysphagia, and severe trismus. On imaging exams, absence of teeth 18 and 48 and purulent collection stores. Treatment was surgical with drainage of the exudate, curettage of the areas of extraction and antibiotic therapy. Associated with the surgical procedure, an evaluation of medical specialties for systemic control of the patient was requested. After 7 days of hospitalization, the patient was discharged, but she continued to return postoperatively. The severe picture presented by the patient shows the magnitude that the odontogenic infection can reach. Postoperative surgical treatment corroborated with antibiotic therapy and systemic control of the patient were decisive. The treatment of pericoronitis before extraction is the decisive factor to avoid infectious processes of the magnitude presented by the patient.